Large rotation of the N-terminal domain of Hsp90 is important for interaction with some but not all client proteins - Daturpalli, Soumya; Knieß, Robert A.; Lee, Chung-Tien; Mayer, Matthias P. (Journal of molecular biology, 2017)
The 90-kDa heat shock protein (Hsp90) chaperones the late folding steps of many protein kinases, transcription factors, and a diverse set of other protein clients not related in sequence and structure. Hsp90's interaction with clients appears to be coupled to a series of conformational changes. How these conformational changes contribute to its chaperone activity is currently unclear. Using crosslinking, hydrogen exchange mass spectrometry, and fluorescence experiments, we demonstrate here that the N-terminal domain of Hsp90 rotates by approximately 180° as compared to the crystal structure of yeast Hsp90 in complex with Sba1 and AMPPNP. Surprisingly, Aha1 but not Sba1 suppresses this rotation in the presence of AMPPNP but not in its absence. A minimum length of the largely unstructured linker between N-terminal and middle domain is necessary for this rotation, and interfering with the rotation strongly affects the interaction with Aha1 and the intrinsic and Aha1-stimulated ATPase activity. Surprisingly, suppression of the rotation only affects the activity of some clients and does not compromise yeast viability.
Available online 28 March 2017
Gesehen am 06.08.2018